Los romances «añadidos» del Cancionero de romances: una hipótesis sobre el fragmentismo del romancero viejo - Higashi, Alejandro (El Colegio de México, 2020)
I analyze the patterns of rewriting evident in the different versions of several romances published in the first edition of Martín Nucio’s Cancionero de romances and in the second, of 1550. They are gruoped together under the concept of publishers’ versions (those that are introduced in the same printing presses, with the purpose of offering improved texts). Although it is very likely that some of these versions come from a courtly oral substrate, the vast majority are textual modifications made in order to offer more extensive and detailed versions. This phenomenon forces us to rethink the fragmentary nature attributed to the romancero viejo.